Budaya Jawa Ibu Postpartum Di Desa Candirejo Kecamatan Ngawen Kabupaten Klaten - Sugita Sugita; Nurul Herlina Widiastuti (Jurnal Kebidanan dan Kesehatan Tradisional, 2016)
Abstract: Java Culture, Mrs. Post Partum. The purpose of this study is to describe the culture of Java on postpartum mothers in the village Candirejo Ngawen District of Klaten district. This research is descriptive quantitative research subjects across the capital after the postpartum period ending at 24 samples. Technical analysis of the data used is descriptive test. The results showed that 16.66% of mothers after the postpartum period wear pilis 0-40 days, 25% use them less than 40 days, 37.5% were taking parem in the hands and feet for 40 days, 75% drink herbal rice kencur, 87, 5% herbal drink wejahan, 37.5% herbal drink papaya leaves, 8.33% herbal drink turmeric tamarind, ginger herbal drink 4,16%, 37.5% herbal drink uyup-uyup, 37.5% do masage, 58, 33% do walik bye at the time selapanan, 37.5% were taking octopus knot, wearing a corset 8.33%, 50% wear stagen 4 meters long, 41.66% were taking stagen along 10 meters, 50% do kempitan less than 40 day, 95.83% did sit senden less than 40 days, 66.66% abstain from eating spicy, 33.33% abstaining stimulating, 4.16% abstain from drinking a lot, 12.5% abstinence drinking ice, 8.33% abstain from eating sugary foods, 87.5% sat straight legs, a 100% sat feet together, parallel, not hanging and 75% sat with his feet propped up a small chair.